A Proposal for an Austrian Nursing Minimum Data Set (NMDS) - Ranegger, R.; Hackl, W.O.; Ammenwerth, E. (Applied Clinical Informatics, 2014)
Objective: Nursing Minimum Data Sets can be used to compare nursing care across clinical populations, settings, geographical areas, and time. NMDS can support nursing research, nursing management, and nursing politics. However, in contrast to other countries, Austria does not have a unified NMDS. The objective of this study is to identify possible data elements for an Austrian NMDS.Methods: A two-round Delphi survey was conducted, based on a review of available NMDS, 22 expert interviews, and a focus group discussion.Results: After reaching consensus, the experts proposed the following 56 data elements for an NMDS: six data elements concerning patient demographics, four data elements concerning data of the healthcare institution, four data elements concerning patient’s medical condition, 20 data elements concerning patient problems (nursing assessment, nursing diagnoses, risk assessment), eight data elements concerning nursing outcomes, 14 data elements concerning nursing interventions, and no additional data elements concerning nursing intensity.Conclusion: The proposed NMDS focuses on the long-term and acute care setting. It must now be implemented and tested in the nursing practice.Citation: Ranegger R, Hackl WO, Ammenwerth E. A proposal for an austrian nursing minimum data set (NMDS): A Delphi study. Appl Clin Inf 2014; 5: 538–547 http://dx.doi.org/10.4338/ACI-2014-04-RA-0027
Keywords: Nursing minimum data set; minimal data set; nursing informatics; health statistics; Austria